2019
DOI: 10.1103/physrevd.100.084044
|View full text |Cite
|
Sign up to set email alerts
|

Self-intersecting marginally outer trapped surfaces

Abstract: We have shown previously that a merger of marginally outer trapped surfaces (MOTSs) occurs in a binary black hole merger and that there is a continuous sequence of MOTSs which connects the initial two black holes to the final one. In this paper, we confirm this scenario numerically and we detail further improvements in the numerical methods for locating MOTSs. With these improvements, we confirm the merger scenario and demonstrate the existence of self-intersecting MOTSs formed in the immediate aftermath of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 79 publications
3
75
0
Order By: Relevance
“…Methodology.-Our main technical tool is a new method (and software) for locating MOTSs numerically which is capable of finding even very highly distorted MOTSs [38][39][40]. This is a modification of the commonly used algorithm known as AHFinderDirect [44].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methodology.-Our main technical tool is a new method (and software) for locating MOTSs numerically which is capable of finding even very highly distorted MOTSs [38][39][40]. This is a modification of the commonly used algorithm known as AHFinderDirect [44].…”
mentioning
confidence: 99%
“…Additional resolutions were used to verify convergence. All parameter files are available in the repository [40].…”
mentioning
confidence: 99%
“…We highlight some known features of a binary black hole merger, as described in [48,49,27]. This also serves to set up our notation.…”
Section: Previous Workmentioning
confidence: 99%
“…This also serves to set up our notation. In [48,49], it was found that there is a connected sequence of MOTSs, which interpolate between the initial and final states of the merger (two separate BHs to one BH, respectively) [48,49]. The dynamics are as follows: Initially, there are two BHs with disjoint MOTS (which are AHs at this point [27]), S 1 , and S 2 , one around each BH.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation